First investigation of Staphylococcus argenteus in a Brazilian collections of S. aureus isolated from bovine mastitis - Rossi, Bruna F. [UNESP]; Bonsaglia, Érika C. R. [UNESP]; Castilho, Ivana G. [UNESP]; Dantas, Stéfani T. A. [UNESP]; Langoni, Hélio [UNESP]; Pantoja, José C. F. [UNESP]; Júnior, Ary Fernandes [UNESP]; Gonçalves, Juliano L.; Santos, Marcos V.; Mota, Rinaldo A.; Rall, Vera L. M. [UNESP] (Springer Nature, 2020)
Background: Staphylococcus argenteus is a new specie positive coagulase staphylococci. We investigate the presence of S. argenteus in isolates previously classified as S. aureus, obtained from the milk of cows with mastitis in Brazil. Results: Among 856 S. aureus tested in chocolate agar, tryptone soya agar and salt egg yolk agar, white or colorless colonies were observed in 185 (21.6%) isolates. Regarding the ctrOPQMN operon, 111 (60%) presented the complete cluster. Despite some missing genes in this cluster, the remaining strains (74) were confirmed as S. aureus using the nrps gene. Conclusions: As far as we know, this is the first review of S. aureus collection in Brazil and S. argenteus does not appear to be a significant problem in Brazilian herds.
Keywords: nrps gene; S. aureus complex; Salt egg yolk agar; Staphyloxanthin